2012
DOI: 10.3354/dao02428
|View full text |Cite
|
Sign up to set email alerts
|

Influence of disseminated neoplasia, trematode infections and gametogenesis on surfacing and mortality in the cockle Cerastoderma edule

Abstract: Cerastoderma edule is a widely distributed bivalve mollusc, commercially exploited throughout Europe and is also an important food source for birds and crustaceans. Recently, mass surfacing and mortalities of cockles have been observed and reported at sites in Ireland and elsewhere, particularly in the summer months. One such site is Flaxfort Strand, Courtmacsherry Bay, County Cork, Ireland, an important feeding area used by many seabirds during the summer months. For the past few years large numbers of surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 46 publications
7
29
0
Order By: Relevance
“…There is a not clear pattern regarding sex and occurrence of DN. Some studies reported no association between sex and DN prevalence in softshell clams M. arenaria (Brown et al, 1979;Potts, 1996), in mussels M. trossulus (Cosson-Mannevy et al, 1984) and in cockles C. edule (Iglesias, 2006;Morgan et al, 2012). Nevertheless, Brousseau and Baglivo (1994) found that female clams had a significantly lower occurrence of DN than male clams in three populations of M. arenaria from Connecticut.…”
Section: Determinant Factors On the Occurrence Of Disseminated Neoplasiamentioning
confidence: 89%
See 3 more Smart Citations
“…There is a not clear pattern regarding sex and occurrence of DN. Some studies reported no association between sex and DN prevalence in softshell clams M. arenaria (Brown et al, 1979;Potts, 1996), in mussels M. trossulus (Cosson-Mannevy et al, 1984) and in cockles C. edule (Iglesias, 2006;Morgan et al, 2012). Nevertheless, Brousseau and Baglivo (1994) found that female clams had a significantly lower occurrence of DN than male clams in three populations of M. arenaria from Connecticut.…”
Section: Determinant Factors On the Occurrence Of Disseminated Neoplasiamentioning
confidence: 89%
“…DN was described at consistently high prevalence (>20%, but frequently over 40% in some samples) in cockles C. edule from the European Atlantic coast, sometimes associated with abnormal mortalities Ordás and Figueras, 2005). DN in cockles was reported in southern Ireland, in different locations of County Cork at an overall prevalence of 22% (range: 0-72%) Mulcahy, 1984, 1988b;Morgan et al, 2012). In France, cockles from Brittany had an overall prevalence of 4% (range: 2-46%) ) and from Arcachon Bay, monthly prevalence ranged from 2.2% to 13.6% (Le Grand et al, 2010).…”
Section: Epidemiologymentioning
confidence: 93%
See 2 more Smart Citations
“…No parasites, pathogenic states or disease were found in any of the soft shell clams sampled in either of the two sites in the current study, despite a heavy prevalence of trematodes, neoplasia and Nematopsis spp. in Cerastoderma edule within the same area (Morgan et al, 2012), and Ostreid Herpes Virus previously identified in Crassostrea gigas in Bannow Bay .…”
Section: Discussionmentioning
confidence: 99%